Digital Social Capital and the Reconfiguration of Global Education Economies: A Theoretical Inquiry - Mowafg Masuwd (Lafadz Jaya Publisher, 2025)
The rapid integration of digital technologies has transformed global education systems, reshaping the ways learners, educators, and institutions interact and create value. This theoretical inquiry explores the role of digital social capital in the reconfiguration of global education economies, emphasizing its effects on knowledge flows, pedagogical innovation, credentialing, and institutional strategy. Drawing on a comprehensive review of interdisciplinary literature from sociology, economics, education studies, and information and communication technology (ICT), the study develops a conceptual framework that positions digital social networks as both a social and economic asset. The analysis highlights the opportunities and challenges associated with digital social capital, including its potential to enhance learning outcomes, generate economic value, and expand global connectivity, as well as its dependence on access, digital literacy, and policy frameworks. This paper contributes to the literature by providing a multi-dimensional theoretical model that explains how digital social capital mediates structural transformations in education and offers insights for policymakers, educators, and institutions seeking to leverage digital networks for equitable and sustainable educational outcomes. The findings also underscore the need for inclusive policies to mitigate digital inequalities and optimize the benefits of networked learning in a global context.